Philip Sidney’s Poetics in the Context of Ancient and Continental Examples - Kastnerová, Martina (American & British Studies Annual, 2017)
The study deals with the main tenets of Philip Sidney’s poetics on the basis of The Defence of Poesy and his poetry (mainly Astrophil and Stella) in the context of Elizabethan considerations of the classical aesthetic concepts (especially that of Aristotle and Horace) and some of the Renaissance continental examples. Sidney’s The Defence of Poesy represents a fundamental step in establishing poetry as the creator of its own world, its so-called second nature, and points out poetry’s ability to create figures and imitate reality; thus the main value of poetry lies in creating clear rhetorical images of moral truth. So Sidney’s poetics plays an important role in establishing English poetry as a device of the national cultural and social autonomy.